(untitled) (International relations and international law Journal, 2018)
Start of the active phase of the transformation of the system falls on the sunset period of the socialist system in Eastern Europe and the USSR, namely, during the peaceful revolutions in the late 1980s. («Velvet» and «Tender» revolutions/ czech. – Sametová revoluce; slovakian – Nežná revolúcia). After a quarter of a century it is time to rethink the results of the complex process of transition of 90‘s - early 2000‘s. Moreover, „while Russia and Eurasia is an example of a chaotic, uncertain situation«, are in the process of „chaos« or „controlled chaos«, the Eurasian space continues to experience events, full of contradictions and are not always amenable to logical explanation. At the end of the second decade of the new century, the world was confronted with a peculiar method of „dominoes«, when one of the „chaos« (the collapse of the Soviet Union), followed by another „chaos«. At the beginning of the twenty-first century in the studies of international processes were changed scientific paradigms. In the literature, the impact of the newly conceptualized processes „destruction« and a storage capacity for the following changes in the international system, in the development of Eastern European States and the former Soviet Union countries. Key words: transformation, «velvet/tender revolution», «controlled chaos», synergetic approach, Eastern Europe, Central Asia.